EDUKASI HUKUM TENTANG INTOLERANSI DAN PERBUATAN BULLYING BERSAMA MAHASISWA SEBAGAI PIONER DI LINGKUNGAN KAMPUS - Febri Handayani; Lysa Angrayni (Komunitas Manajemen Kompetitif, 2026)
Higher education, as an academic space that upholds the values of humanity, diversity, and freedom of thought, still faces social issues such as intolerance and bullying on campus. This phenomenon not only affects victims' psychological well-being but also hinders the creation of an inclusive and democratic academic climate, student social relations, and the quality of higher education. This community service activity aims to improve students' legal understanding of intolerance and bullying, foster legal awareness, and shape students as pioneers in building a humanistic and anti-discriminatory campus culture. The results of the activity showed an increase in participants' understanding of the forms of intolerance and bullying, the legal consequences for perpetrators, and the importance of students' roles in preventing and handling cases on campus. In addition, this activity fostered a collective commitment among students to become agents of change in building an academic culture that respects diversity and upholds human rights. Thus, student-participatory legal education is an effective strategy and supports the development of existing digital media as an educational tool to strengthen legal awareness and create a safe, inclusive, and civilized campus environment.